Strategic Management for An Entrepreneurial Venture (Case Study: Eternitea) - Puspita, Indah; Larso, Dwi (The Indonesian Journal of Business Administration, 2014)
Abstract. The competition in the RTD (Ready-To-Drink) milk tea currently in Indonesia is rapidly increasing. Until April 2013 Eternitea, an RTD milk tea company, has been growing, but in May 2013 the sales was decreased and not able to reach its target. The business issues of Eternitea are: (1) how to increase Eternitea sales to reach its target sales, and (2) how to develop Eternitea in order to survive and continue to grow in the long-term. The external and internal analyses, followed by SWOT analysis, are used to analyze the business situation. The roots of problems that are found are: (1) limited production capacity because of no employees and (2) no established strategic management processes. Strategic formulation is used to find and analyze the business solution. From EFAS and IFAS, the most appropriate business strategy to be implemented by Eternitea is a growth strategy, while considering the companyâ€™s external and internal strategic factors, the best competitive strategy is differentiation focus. Eternitea should focus to serve middle-to-higher-income potential customers and create differentiation through its product and distribution. There are three alternative growth strategies that will be implemented by Eternitea in order to survive and continue to grow in long-term: (1) product development for short-term, (2) market penetration for medium-term, and (3) market development for long-term. In conclusion, Eternitea should hire employees in the field of marketing and operation.Â Key words: Eternitea, Ready-To-Drink, Strategic Management